Cross-functional decision support systems for a supplier selection problem. (21st June 2011) - Miah, Shah Jahan; Huth, Michael
In supply chain management, how to determine appropriate suppliers has been a key challenge in strategic decision making. Supply chain managers need to explore options in selecting suitable suppliers that best fulfil the requirements in a competitive environment. This article focuses on how the supplier selection process can be delegated to different organisational levels and to different functional or divisional units within a company. We demonstrate how this de-centrally executed selection process can be supported by a new type of decision support system (DSS) platform, in which cross functional decision making on different managerial levels can be supported. We demonstrate the effectiveness of this type of DSS for supplier selection using a widely used multi-attribute utility approach. The applicability of such an approach will be demonstrated using a subset of sample data from a real-world project.